Portée de l'archéoentomologie dans l'étude des maisons hivernales inuites (période de contact à Dog Island, Labrador, 17e et 18e siècles) - Lalonde, Olivier (Université Laval, 2020)
An archaeoentomological analysis was conducted on sediment samples collected from three Inuit winter houses located at Oakes Bay 1, in the Nain region, Labrador. The analysis’ primary goal is to contribute new perspectives to research concerning the reorganization of Labrador Inuit winter houses and winter households during the 17th and 18th centuries, a significant period of transition in their history. Secondly, the project seeks to explore the potential of archaeoentomology to contribute to archaeology in the Arctic and Subarctic regions. Following an in depth analysis of the ecology of insects collected from Oakes Bay 1, we conclude that archaeoentomological assemblages from Inuit contexts are not well suited for the study of domestic living conditions. Instead, archaeoentomological assemblages were more productively employed to document the use of a variety of food and raw materials in the house, to document site formation and to shed light on temporary and permanent abandonment of winter houses, a critical aspect of the occupation history of all archaeological sites that is difficult to observe through conventional archaeological field methods. Cette recherche consiste en une analyse archéoentomologique portant sur des échantillons prélevés dans trois maisons hivernales inuites d’Oakes Bay 1, dans la région de Nain, au Labrador. L’analyse a deux objectifs : contribuer à la recherche sur la période transitoire critique que traversent les Inuits du Labrador entre le 17e et le 18e siècle, qu’on observe principalement dans un changement structural des maisons hivernales et explorer le potentiel de l’archéoentomologie dans les régions arctiques et subarctiques pour combler les lacunes dans nos interprétations. Une analyse approfondie de l’écologie des insectes indique que les assemblages archéoentomologiques provenant de contextes inuits ne sont pas les plus aptes à étudier les conditions de vie à l’intérieur des maisons. En revanche, ils servent à mieux comprendre l’utilisation de matériaux divers lors de ...